Status Resiko 4 Terlalu (4T) Pada Ibu Hamil Dilihat Dari Pengetahuan dan Sikapnya di Puskesmas Kecamatan Pondok Aren Tahun 2016 - Siti Dariyani; Restu Octasila (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT Introduction, One of the indirect causes of maternal death is too long a mother, too young, too old, too close and too often. Often complications are triggered by this 4T risk. Research Methodology, research design is analytical. The number of research samples is 144 respondents, the sampling technique was accidental sampling. Data analysis using chi-square. Research Results, the presentation of respondents who were at risk of 4T risk status was still 42.3%, the level of knowledge was good 87.5%, the percentage of positive attitudes was 83.3%. The results of chi-square analysis of knowledge and attitudes with 4T risk status obtained p value 0.339 and 1,000 Conclusions, there was no significant relationship between knowledge and attitudes of pregnant women on the 4T risk status. before pregnancy occurs. Keyword: Knowledge, attitude, risk status 4T